Pengaruh Pelatihan Teknik Announcing Terhadap Peningkatan Kualitas Pemandu Acara (MC) Bagi Remaja Kampung Cerdas - Azhar Hutomo (Jurnal Komunikasi, 2019)
Announcement technique learning is not only important for radio broadcasters and television show guides. But it can be given as early as possible to children and adolescents. This is because this technique can be used as a tool for developing self-confidence in socializing and speaking in any context. This study aims to determine the effect of Announcing Technical Training on Quality Improvement of MCs. This type of research is quantitative. The data source of this study is primary data using the Smart Village Youth Youth as a sample. Data were collected using saturated sampling with respondents as many as 30 youth youth. This study uses simple linear regression analysis. The findings of this study indicate that the Announcing Technical Training affects the Quality Improvement of Hosts (MC) for Smart Village Adolescents